Strategies of Decarbonization for a Sustainable Future - Policy Brief - Bento, N.; Fontes, M.; Mário Vale; Sousa, C.; Ribeiro, R.; Alves, T. (Sus2Trans project, 2024)
Global emissions are rising, and the Paris Agreement's goals — to reduce greenhouse gas emissions by over 40% by 2030 — are becoming increasingly critical. The importance of studying different decarbonization strategies lies in their potential to provide tailored and effective solutions for achieving sustainability. By understanding the diverse pathways available, decision-makers in public, private, or collective organizations can implement the most suitable measures to meet their specific regional needs. This Policy Brief summarizes the key lessons from the FCT-funded "Sustainable Transformative Transitions" Sus2Trans Project.